Functional Linguistics
Functional Linguistics publishes scholarly articles and reviews in the broad area of functional studies, with a special focus on systemic functional linguistics. The journal aims to provide a platform for the exploration of language and linguistic issues from a functional and meaning-oriented perspective. Areas to be covered in this journal include: language and context, functional grammar, semantic variation, discourse analysis, multimodality, register and genre analysis, educational linguistics, etc.